A Combined Method to Predict Impact Pressure on Planing Craft - Tahmasvand Hossein; Zeraatgar Hamid (Polish Maritime Research, 2021)
Prediction of the pressure distribution on a planing craft in waves deeply affects its structural design and safe operation. In this paper, the possibility of pressure prediction for the planing craft in waves is studied. A combined method is formulated by which craft motions in waves are computed using a 2.5D method, and the impact pressure is anticipated by the equivalent wedge method. Experiments are conducted to record the vertical acceleration and pressure time trends on a model. Comparing the results of the combined method with the experiments indicates that this approach successfully predicts the heave and pitch motions and the time evolution of the acceleration and pressure. The method presents good estimations for the peaks of the acceleration and pressure. Using the combined method, a parametric study on maximum peak acceleration and pressure is also conducted for various forward velocities and wave heights. It has been shown that the combined method is a fast and reliable tool for maximum peak pressure prediction. The method may be employed for structural design and optimization.